2018
DOI: 10.1016/j.bbi.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin treatment leads to better cognitive and mood function in a model of Gulf War Illness with enhanced neurogenesis, and alleviation of inflammation and mitochondrial dysfunction in the hippocampus

Abstract: Diminished cognitive and mood function are among the most conspicuous symptoms of Gulf War Illness (GWI). Our previous studies in a rat model of GWI have demonstrated that persistent cognitive and mood impairments are associated with substantially declined neurogenesis, chronic low-grade inflammation, increased oxidative stress and mitochondrial dysfunction in the hippocampus. We tested the efficacy of curcumin (CUR) to maintain better cognitive and mood function in a rat model of GWI because of its neurogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 78 publications
6
84
0
1
Order By: Relevance
“…Curcumin‐loaded nanoparticles powerfully induce adult neurogenesis and reverse cognitive deficits in an Alzheimer's disease model via the activation of WβC‐signalling pathway (Tiwari et al, , ). The ability of curcumin treatment to ameliorate cognitive and mood function was previously associated with increased neurogenesis as well as mitigation of inflammation and mitochondrial dysfunction in the rodent hippocampus (Kodali et al, ).…”
Section: Therapeutic Modulation Of Wnt/β‐catenin Signallingmentioning
confidence: 97%
See 1 more Smart Citation
“…Curcumin‐loaded nanoparticles powerfully induce adult neurogenesis and reverse cognitive deficits in an Alzheimer's disease model via the activation of WβC‐signalling pathway (Tiwari et al, , ). The ability of curcumin treatment to ameliorate cognitive and mood function was previously associated with increased neurogenesis as well as mitigation of inflammation and mitochondrial dysfunction in the rodent hippocampus (Kodali et al, ).…”
Section: Therapeutic Modulation Of Wnt/β‐catenin Signallingmentioning
confidence: 97%
“…Kaur et al (2017) addressed the potential of coupling optogenetics and light-sheet microscopy to study Wnt signalling during embryogenesis, showing that WβC-signalling is required not only for Drosophila pattern formation, but also for maintenance later in development. Additionally, Zhang, Huang, et al (2016c) Ameliorates cognitive function, enhances neurogenesis, mitigates inflammation and mitochondrial dysfunction in hippocampus in a rodent model of gulf war illeness; WβC-AC involvement to be elucidated Kodali et al (2018) Exercise, environmental enrichment…”
Section: Optogeneticsmentioning
confidence: 99%
“…Six hours after SE, animals in both naïve and SE groups underwent intracardiac perfusions with 4% paraformaldehyde. The brains were dissected, post-fixed in 4% paraformaldehyde overnight, and processed for sectioning using a cryostat [52][53][54][55][56]. Thirty micrometer-thick coronal sections were cut through the entire forebrain and collected serially in 24-well plates containing the phosphate buffer.…”
Section: Tissue Processing and Immunofluorescence Studiesmentioning
confidence: 99%
“…Optical Z-sections (1-µm thick) were sampled from different forebrain regions using a Nikon confocal microscope [53][54][55][56]. Z-stacks were captured from three different fields in every region of the forebrain for every marker analyzed in the study.…”
Section: Confocal Microscopymentioning
confidence: 99%
“…For GWI patients, the levels of multiple proin ammatory biomarkers in the blood also increased signi cantly 10 . More importantly, enhanced neurogenesis, and alleviation of neuroin ammation by curcumin treatment could leads to better cognitive and mood function in GWI rats 11 . Taken together, the results of these studies have indicated that over activation of neuroin ammation and impaired neurogenesis in the adult hippocampus might be the key biological processes involved in GWI pathophysiology and may as the potential therapeutic targets for treating GWI.…”
Section: Introductionmentioning
confidence: 99%